Preparation of Chitosan Coating Loaded with Cinnamaldehyde-Tannic Acid Nano-emulsion and Its Effect on the Preservation of Chilled Meat - Xingqun DENG; Juan YOU; Ru LIU; Jirawat YONGSAWADIGUL; Tao YIN; Hong YANG (Shipin gongye ke-ji)
In order to extend the shelf life of chilled pork, chitosan coating (CS/CIN-TAs) loaded with cinnamaldehyde (CIN)-tannic acid (TA) nano emulsion was prepared, and the effect of the coating on the preservation of chilled pork was studied. When the mass ratio of TA to CIN was 1:4, the nano emulsion (CIN-TAs) had average particle size of 212.60 nm, PDI value of 0.365, spherical morpholog, and showed well storage stability at 4 ℃. Compared with chitosan coatings, CS/CIN-TAs exhibited much better antibacterial effects against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Moreover, CS/CIN-TAs could more pronouncedly scavenge ABTS+ and DPPH radicals. During storage, CS/CIN-TAs could significantly slow down the decrease of sensory score values, inhibit the increase of pH, thiobarbituric acid content, total volatile basic nitrogen (TVB-N), and total bacterial count, maintain meat color, and effectively inhibit the growth and reproduction of Pseudomonas genus. In terms of preservation, TA and CIN showed a synergistic effect, and the effect of CS/CIN-TAs was concentration dependent. After 9 days of storage, the TVB-N and total bacterial count of the blank group of chilled pork were 15.07 mg/100 g and 6.36 lg CFU/g, respectively, exceeding the limit values in the Chinese National Standard (15 mg/100 g and 6 lg CFU/g). However, after 12 days of storage, the TVB-N and total bacterial count of the CS/CIN-TAs group were still lower than the limit values. The chitosan coating loaded with nano emulsion of cinnamaldehyde and tannic acid could effectively extend the shelf life of chilled pork, and had good application prospects.